Arthroscopic Removal of a Displaced Cannulated Screw after Glenoid Rim Fracture: A Case Report - Elias T. Berning; Thilo Sydow (Journal of Orthopaedic Case Reports, 2013)
Introduction: Internal fixation has been shown to successfully prevent recurrent dislocations after fractures of the glenoid rim. With regards to fixation either suture anchors or screws can be used, depending on the fragment size. Complications regarding suture anchors and their management have been described previously but not the arthroscopic management of screw impingement.Case Report: We present a case of a 70 year old women who suffered from limited range of motion after fixation of a Ideberg III fracture using cannulated screws. X-rays showed one of the screws to be proud. The proud screw could be successfully removed arthroscopically resulting in an improved range of motion, function and decreased pain.Conclusion: Our report describes a possible technique for performing a procedure arthroscopically that used to be done as an open procedure before and highlights it’s limitations.